Adrenal-derived 11-oxygenated 19-carbon steroids are the dominant androgens in classic 21-hydroxylase deficiency. Issue 5 (May 2016) - Turcu, Adina F; Nanba, Aya T; Chomic, Robert; Upadhyay, Sunil K; Giordano, Thomas J; Shields, James J; Merke, Deborah P; Rainey, William E; Auchus, Richard J
Abstract: Objective: To comprehensively characterize androgens and androgen precursors in classic 21-hydroxylase deficiency (21OHD) and to gain insights into the mechanisms of their formation. Design: Serum samples were obtained from 38 patients (19 men) with classic 21OHD, aged 3–59, and 38 sex- and age-matched controls; 3 patients with 11β-hydroxylase deficiency; 4 patients with adrenal insufficiency; and 16 patients (8 men) undergoing adrenal vein sampling. Paraffin-embedded normal (n = 5) and 21OHD adrenal tissues (n = 3) were used for immunohistochemical studies. Methods: We measured 11 steroids in all sera by liquid chromatography-tandem mass spectrometry. Immunofluroescence localized 3β-hydroxysteroid dehydrogenase type 2 (HSD3B2) and cytochrome b5 (CYB5A) within the normal and 21OHD adrenals. Results: Four 11-oxygenated 19-carbon (11oxC19) steroids were significantly higher in male and female 21OHD patients than in controls: 11β-hydroxyandrostenedione, 11-ketoandrostenedione 11β-hydroxytestosterone, and 11-ketotestosterone (3–4-fold, P < 0.0001). For 21OHD patients, testosterone and 11-ketotestosterone were positively correlated in females, but inversely correlated in males. All 11oxC19 steroids were higher in the adrenal vein than in the inferior vena cava samples from men and women and rose with cosyntropin stimulation. Only trace amounts of 11oxC19 steroids were found in the sera of patients with 11β-hydroxylase deficiency and adrenal insufficiency, confirming their adrenal origin. HSD3B2 and CYB5A immunoreactivities were sharply segregated in the normal adrenal glands, whereas areas of overlapping expression were identified in the 21OHD adrenals. Conclusions: All four 11oxC19 steroids are elevated in both men and women with classic 21OHD. Our data suggest that 11oxC19 steroids are specific biomarkers of adrenal-derived androgen excess.